Prospective observational cohort study of 'treatment as usual' over four years for patients with schizophrenia in a national forensic hospital. - Kennedy, Harry; Corvin, Aiden; Davoren, Mary (My University, 2018)
Background: We evaluated change in response to multi-modal psychosocial ‘treatment as usual’ programs offered within a forensic hospital. Methods: Sixty nine patients with a diagnosis of schizophrenia or schizoaffective disorder were followed for up to four years. Patient progress was evaluated using the DUNDRUM-3, a measure of patient ability to participate and benefit from multi-modal psychosocial programs and the HCR-20 dynamic items, a measure of violence proneness. We report reliable change index (RCI) and reliable and clinically meaningful change (RMC). We assessed patients’ cognition using the MCCB, psychopathology using the PANSS. The effect of cognition and psychopathology on change in DUNDRUM-3 was examined using hierarchical multiple regression with age, gender, and baseline DUNDRUM-3 scores. Results: The DUNDRUM-3 changed significantly (p < 0.004, d = 0.367, RCI 32% of 69 cases, RMC 23%) and HCR-20-C (p < 0.003, d = 0.377, RCI 10%). Both cognition and psychopathology accounted for significant variance in DUNDRUM-3 at follow up. Those hospitalized for less than five years at baseline changed more than longer stay patients. Mediation analysis demonstrated that the relationship between cognition and change in violence proneness (HCR-20-C) was both directly affected and indirectly mediated by change in DUNDRUM-3. Conclusions: Change in response to multi-modal psychosocial programs (DUNDRUM-3) reduced a measure of violence proneness over four years. Forensic in-patients’ ability to benefit from psychosocial treatment appears to be a function of the outcome measure used, unit of measurement employed, degree of cognitive impairment, psychopathology, and length of stay. Lower risk of re-offending may be partially attributable to participation and engagement in psychosocial interventions.
PUBLISHED
Keywords: Forensic psychiatry; Treatment; Cognition; Violence risk; DUNDRUM toolkit